2006
DOI: 10.1002/ijc.21938
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of MCF7 breast cancer cells in response to 5‐Fluorouracil: Relationship with cell cycle changes and apoptosis, and identification of novel targets of p53

Abstract: The availability of oral precursors of 5-Fluorouracil (5-FU) and its favorable results in treating advanced breast cancer have renewed the interest in the molecular mechanisms underlying its cytotoxicity. We have compared the changes in cell cycle and cell death parameters induced by 2 different concentrations of 5-FU (IC50 and IC80) in the breast adenocarcinoma cell line MCF7. G1/S cell cycle arrest was associated with both concentrations, whereas cell death was mainly induced after IC80 5-FU. These changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 33 publications
9
46
1
Order By: Relevance
“…The concentration range of free 5-FU was selected based on preliminary experiments, in which increasing concentrations of 5-drug from 0.01 µM to 1 mM were tested in culture. Those drug concentrations were in accordance with data reported in the literature [33][34][35]. The administration of 5-FU 10 μM in solution produced a decrease of the percentage of viability in MCF7 cells, which was between 91 ± 8% and 43 ± 3% after 3 days of incubation.…”
Section: Cell Culture Studiessupporting
confidence: 91%
“…The concentration range of free 5-FU was selected based on preliminary experiments, in which increasing concentrations of 5-drug from 0.01 µM to 1 mM were tested in culture. Those drug concentrations were in accordance with data reported in the literature [33][34][35]. The administration of 5-FU 10 μM in solution produced a decrease of the percentage of viability in MCF7 cells, which was between 91 ± 8% and 43 ± 3% after 3 days of incubation.…”
Section: Cell Culture Studiessupporting
confidence: 91%
“…After culture at different time points, samples were harvested (including detached cells), suspended in phosphate-buffered saline (PBS), fixed in 70% ethanol, and their DNA content was evaluated after PI staining, as described previously (Herna´ndez-Vargas et al, 2006). Fluorescence-activated cell sorting analysis was carried out using a FACScan flow cytometer (Becton Dickinson, San Diego, CA, USA) and CellQuest software.…”
Section: Methodsmentioning
confidence: 99%
“…Three micrograms of total RNA from samples and Universal Human Reference RNA (Stratagene, La Jolla, CA, USA) were used for amplification using the Superscript Choice System (Life Technologies Inc., Gaithersburg, MD, USA) and in vitro transcription with Megascript T7 (Ambion, Austin, TX, USA), as described previously (MorenoBueno et al, 2003;Herna´ndez-Vargas et al, 2006). The cDNA array chip is the CNIO Oncochip manufactured by the CNIO Genomic Unit (http://bioinfo.cnio.es/data/oncochip).…”
Section: Microarrays Hybridization and Data Analysismentioning
confidence: 99%
“…Cancer Cells-Previous studies indicated that ID1 was commonly up-regulated by chemotherapeutic drug treatment (18,19). To evaluate the possible role of ID1 in ESCC, we first analyzed ID1 expression in ESCC tumor tissues and ESCC cell lines Fig.…”
Section: Id1 Expression Was Induced By Etoposide In Esophagealmentioning
confidence: 99%
“…Notably, ID1 was involved in chemotherapy and radiotherapy resistance in human cancers including pancreatic adenocarcinoma, breast cancer, lung cancer, colorectal cancer, and esophageal cancer and becomes a new potential therapeutic target (13)(14)(15)(16)(17). ID1 is transactivated in the context of 5-fluorouracil therapy, which provides a resource for future study addressing the molecular mechanisms of chemotherapy in breast cancer (18). In the study of p53 protecting cells from arsenic caused cell cycle arrest, ID1 is more extensive induced by arsenite in p53 ϩ/ϩ cells rather than p53-deficient cells, which display greater resistance to arsenite-induced mitotic arrest and apoptosis (19).…”
mentioning
confidence: 99%